(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid expansion of startups in India has significantly contributed to economic growth, innovation, and employment generation under the vision of Atmanirbhar Bharat. Indian startups are increasingly promoting employment self-reliance through entrepreneurial opportunities, digital transformation, and innovation-led business models across sectors such as fintech, agritech, healthtech, logistics, and e-commerce. The present study examines the role of Indian startups in generating direct and indirect employment opportunities and evaluates the influence of government initiatives, technological adoption, innovation capability, and financial accessibility on employment self-reliance. The study adopts a descriptive and analytical research design based on both primary and secondary data. Primary data were collected from 200 respondents including startup founders, managers, employees, and entrepreneurship experts through structured questionnaires. Secondary data were gathered from government reports, journals, books, research articles, Startup India databases, and policy documents. Statistical tools such as percentage analysis, correlation analysis, regression analysis, and chi-square tests were applied using SPSS and MS Excel.The empirical findings reveal that government support has a positive relationship with startup sustainability and employment generation (r = 0.68, p < 0.05). Innovation capability also demonstrates a significant impact on employment creation (R² = 0.57), while digital technology adoption contributes substantially to startup growth and labor scalability. The study further identifies that startups have generated both direct employment in technology, operations, and management and indirect employment through logistics, supply chains, digital marketing, and gig-based platforms. The findings also indicate that rural startups and women-led enterprises are increasingly contributing toward inclusive development and reduction of rural-to-urban migration.However, startups continue to face challenges related to funding accessibility, workforce skill gaps, cybersecurity risks, regulatory complexity, and social security concerns in the gig economy. The study concludes that a strong startup ecosystem supported by policy reforms, digital infrastructure, industry-academia collaboration, and innovation-oriented education can significantly strengthen employment self-reliance and sustainable economic development in India.